2017
DOI: 10.3389/fmicb.2017.01224
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Association Study to Identify Diagnostic Markers for Human Pathogenic Campylobacter jejuni Strains

Abstract: Campylobacter jejuni is a leading human enteric pathogen worldwide and despite an improved understanding of its biology, ecology, and epidemiology, limited tools exist for identifying strains that are likely to cause disease. In the current study, we used subtyping data in a database representing over 24,000 isolates collected through various surveillance projects in Canada to identify 166 representative genomes from prevalent C. jejuni subtypes for whole genome sequencing. The sequence data was used in a geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 41 publications
(50 reference statements)
0
51
0
1
Order By: Relevance
“…Consequently, MST C. jejuni strains are more likely to be transmitted to humans than stress-sensitive strains because these strains might be enriched and form unique clones by repeating the cycle of environmental survival, transmission, and human infection. The predominant CGF subtypes in MST clades (0169.001.002, 0044.003.001, and 0083.001.002) are not only prevalent in the CGF collection of human clinical C. jejuni strains in Alberta but also in the Canadian Campylobacter CGF database, which contains CGF information for >25,000 C. jejuni strains from foods, animals, humans, and environmental samples across Canada ( 21 ). Presumably, the level of stress tolerance for clinical strains will be different from that for nonclinical strains because clinical strains have already undergone a range of stress conditions during transmission and infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, MST C. jejuni strains are more likely to be transmitted to humans than stress-sensitive strains because these strains might be enriched and form unique clones by repeating the cycle of environmental survival, transmission, and human infection. The predominant CGF subtypes in MST clades (0169.001.002, 0044.003.001, and 0083.001.002) are not only prevalent in the CGF collection of human clinical C. jejuni strains in Alberta but also in the Canadian Campylobacter CGF database, which contains CGF information for >25,000 C. jejuni strains from foods, animals, humans, and environmental samples across Canada ( 21 ). Presumably, the level of stress tolerance for clinical strains will be different from that for nonclinical strains because clinical strains have already undergone a range of stress conditions during transmission and infection.…”
Section: Discussionmentioning
confidence: 99%
“…Strains in CGF subtype 0044.003.001 in MST clade III were highly tolerant to multiple stresses, including PAA, freezing, and heat treatment ( Figure 4 ). The CGF subtype 0044.003.001 was commonly found in human clinical cases in Alberta ( Figure 5 , panel B) and Canada ( 21 ). This CGF subtype is detected more frequently in human clinical cases (59.0%) than in animals (40.5%) in the Canadian Campylobacter CGF database ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of accessory genes in host adaptation is not limited to S. enterica Typhimurium. Recent studies focused on the pangenome of Campylobacter jejuni showed that hostsegregating genomic factors located in the accessory genomes constitute epidemiological markers for source attribution [12,40].…”
Section: Source Prediction Of Strains Using Accessory Genes As Predicmentioning
confidence: 99%
“…The first successful GWAS in humans was published in 2005 and examined 96 patients with age-related macular degeneration, a condition that leads to vision loss in older adults, and 50 age-matched controls ( Klein et al, 2005 ; Read and Massey, 2014 ). GWAS can identify genetic factors underlying important phenotypes, but have rarely been applied to bacteria ( Sheppard et al, 2013 ; Buchanan et al, 2017 ). The application of GWAS to microorganisms is a potentially powerful approach to rapidly identifying genetic factors that mediate heritable phenotypic variation ( Muller et al, 2011 ; Connelly and Akey, 2012 ; Dalman et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%